The use of blog to improve students' writing ability in explanation text - Shintia Nur Salsabilla; Patuan Raja; Khairun Nisa (U-Jet Unila Journal of English Language Teaching, 2024)
The research aimed to find out whether there was a significant improvement in students’ writing abilities after using a blog as media in teaching writing of explanation text, and also to find out which aspect of writing improved the most after using a blog as media. The sample of this research was twenty-seven students of the XI.11 class at SMAN 7 Bandar Lampung. This research used quantitative research with one group pre-test and post-test design and the data was analyzed by using a paired sample t-test. The result showed a significant improvement in students’ writing between the pre-test and the post-test after the students were taught by using a blog in writing explanation text. The average score of the post-test (78.57) was higher than the pre-test (67.81). By using a t-test, it was found that the t-value (61.935) was higher than the t-table (1.7056). From the research, it was also found that the mechanics aspect was the aspect that improved the most with a gain of 1.0 or 20% over content, organization, vocabulary, and language use. Therefore, it can be concluded that the blog effectively improved students’ writing ability in explanation text.